2013
DOI: 10.37156/relea/2013.16.045
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Empirical Relationship Between Non-Science Majoring Undergraduate Learners’ Spatial Thinking Skills and Their Conceptual Astronomy Knowledge

Abstract: A comunidade da educação em astronomia tem suposto de forma implícita que o aprendizado da astronomia consiste em um domínio conceitual fundamentado no raciocínio espacial. Como um primeiro passo para identificar formalmente uma relação empírica entre estas duas coisas, utilizamos como amostra os estudantes de graduação de carreiras não científicas de um curso exploratório em uma universidade norte-americana do meio-oeste de médio porte com programa de Doutorado em andamento, onde estes estudantes foram submet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
1
12
0
4
Order By: Relevance
“…From extensive teaching experience and research, this model, where disciplinary discernment and extrapolating three dimensionality are assumed equally important as disciplinary declarative knowledge, has been found effective for teaching and learning astronomy and physics at the university level [1,2,10,37,97,139,140]. It may also be possible that the model would apply to other science subjects as well, in particular where one cannot directly see different phenomena, such as atomic interaction in chemistry, see, for example, Refs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From extensive teaching experience and research, this model, where disciplinary discernment and extrapolating three dimensionality are assumed equally important as disciplinary declarative knowledge, has been found effective for teaching and learning astronomy and physics at the university level [1,2,10,37,97,139,140]. It may also be possible that the model would apply to other science subjects as well, in particular where one cannot directly see different phenomena, such as atomic interaction in chemistry, see, for example, Refs.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a novice needs to learn how to read and use all the different disciplinary-specific semiotic resources that constitute the disciplinary discourse of astronomy [6][7][8][9]. Moreover, research has shown that multidimensional (MD) thinking of space, or extrapolating three dimensionality from one-or two-dimensional semiotic resources is both very important and very difficult for students to master [1,3,[10][11][12][13]. These difficulties taken into account makes it challenging for new-to-the-discipline students to learn astronomy, since not only does the student need to learn disciplinary declarative knowledge, but they need to learn to "read" all the different highly specialized disciplinary-specific semiotic resources that astronomers use to communicate within the discipline [8,9,[14][15][16][17].…”
Section: A Learning Astronomymentioning
confidence: 99%
See 2 more Smart Citations
“…Uzamsal akıl yürütme becerisi zihinsel olarak uzayda nesneleri konumlandırma, döndürme, hareket ettirme durumları ve perspektif ile ilişkili bir düşünme şekli olarak tanımlanabilir (Heyer, 2012). Uzamsal düşünme, mekân kavramları, görselleştirme ve akıl yürütme süreçlerinin yapılandırmacı yaklaşım temelli üç bileşene dayanmaktadır (NRC, 2006).…”
Section: Uzamsal Akıl Yürütmeunclassified